ANTONYMY IN PHRASEOLOGY - Visola SAMADOVA (Scholar Express Journal, 2023)
In is article is discussed antonymy and opposite meanings in phraseological units.Phraseological antonyms can be in one or two phraseologisms.In this article emphasized their usage
Keywords: Phraseology; opposite meaning; antonymy